DOES MICROANGIOPATHY INFLUENCE ARTERIAL PRESSURE IN IGA NEPHROPATHY?. (April 2021) - Mannai, Khouloud; Hajri, Malika; Gaied, Hanene; Jerbi, Mouna; Harzallah, Amel; Bacha, Mouhamed Mongi; Trabelsi, Raja; Lounissi, Mondher; Barbouch, Samia; Hedri, Hafedh; Kaaroud, Hayet; Laabidi, Jannet; et al.
Abstract : Objective: This study aimed to establish clinical particularities of patients with primitive IgA nephropathy (IgAN) in case of associated thrombotic microangiopathy (TMA); comparatively with patients without TMA. Design and method: We compared two groups of patients diagnosed with primitive IgAN, from 1995 to 2017. The group1 (G1) comprised all patients with at least one TMA lesion in their renal biopsy. The group 2 (G2) was a randomly chosen sample of patients without TMA. Inclusion criteria were: patients older than 16, and followed up by our team. Exclusion criteria were: secondary IgAN or IgA vascularites, incomplete files and inconclusive IF results. We collected the initial clinical parameters. Then, using the "U" test of Mann-Witney test, we compared the two groups. Results: We selected 50 patients for G1 and 74 patients for G2. Baseline characters of all subjects were: mean age 33, men to women ratio 1.95, mean BMI 24.6 [17–38], mean albuminemia 33 [8–53] g/l, median serum creatinine (SCr) 207 [49–1800]μmol/l, mean eGFR 47 [2–156] ml/min and mean proteinuria 2.9 [0–11] g/day. Mean systolic and diastolic pressure were 139 [90–200] and 85 [50–120] mmHg. Seventy two patients (58%) had hypertension: grade 1, grade 2 and grade 3 for 23.4%, 23.4% and 11.3%. Comparing the two groups (G1 vs G2) the difference was significant for: systolic pressure (p = 0.000, 155 vs 128 mmHg), diastolic pressure (p = 0.000, 93 vs 79 mmHg), hypertension frequency (p = 0.000, 96% vs 32%), grade 2 hypertension (p = 0.000, 38% vs 13.5%), grade 3 hypertension (p = 0.000, 24% vs 2.7%) and SCr (p = 0.000, 501 vs 231 μmol/l). There was no significant difference forage (p = 0.10), BMI (p = 0.26), albuminemia (p = 0.14) and proteinuria (p = 0.059). Conclusions: Founding a TMA lesion in our patients' biopsies should alert us to a more severe form of IgAN, with a more frequent hypertension and more advanced renal failure.